Pilot interventions to improve the sleep/wake habits of elite adolescent athletes : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Public Health at Massey University, Wellington, New Zealand - Steenekamp, Travis (Massey University, 2023)
Both adolescent and athlete populations have been identified as at-risk groups when it comes to sleep timing, duration and quality. The aetiology of sleep issues within these populations is disparate, leading to the question of whether adolescent athletes are at particular risk considering that they span both groups. Few studies, however, have investigated the sleep patterns and behaviours of elite adolescent athletes during their everyday lives. Fewer still have attempted to intervene to improve sleep/wake patterns and behaviour where sleep concerns have been identified within adolescent athlete cohorts. This thesis comprised two studies, the first with a group of elite adolescent swimmers and the second with rowers. Swimmers and rowers were chosen as both sporting codes have traditionally high early morning training demands. Early morning training has been identified as a predominant driver of sleep loss for athlete groups making these cohorts of particular interest. Both studies included baseline monitoring for two weeks to identify the athletes’ typical sleep patterns during a normal training phase that took place during the school term. Following baseline, both athlete groups received educational training on sleep with specific sleep advice being tailored to each group using data gathered during baseline. In addition to the sleep educational material, the swimmers also had one of their early morning training sessions moved to another day of the week to try and provide them with consecutive days free of early morning training while the rowers received blue light-blocking glasses to try to limit night-time exposure to blue light. Baseline data from both groups revealed that sleep timing as well as sleep duration varied significantly across the days of the week. Sleep duration was significantly truncated on school nights before early morning training (6.7 hours) compared to school nights before mornings without training (8.8 hours). The curtailed sleep was linked to significantly earlier wake-up times while bedtimes remained constant. Classic patterns of social jetlag were evident over the weekend. The introduction of educational material in addition to training rescheduling did not result in a significant change to swimmers’ sleep duration or sleep quality. Swimming performance also remained unchanged throughout the 6 week's intervention. A positive sleep behavioural change was noted with device use before bedtime with the swimmers reducing their screen time by 24% over the intervention period. Similarly, the educational material coupled with blue light-blocking glasses did not significantly change actigraphic measures of sleep timing or duration. A reduction was found, however, concerning self-reported measures of fatigue and muscle soreness when comparing intervention to baseline ratings. Unlike the swimmers, the rowers did not significantly reduce their device use before bedtime. The findings of the studies in this thesis elucidate the challenge that early morning training poses for the sleep of adolescent athletes. The adverse consequences of inadequate and disrupted sleep patterns during adolescence are well documented and confirm that significant attention should be paid to optimising the scheduling of training for adolescent athletes. The high prevalence of early morning training sessions is the result of tradition and overloaded adolescent schedules. Creative and careful solutions that involve all stakeholders need to be found to reduce the need for early morning training sessions.
Keywords: Teenage athletes; Health and hygiene; Sleep disorders in adolescence; Early rising; New Zealand; 420702 Exercise physiology